(untitled) (Fiep Bulletin - online, 2016)
This article aims to elucidate by statistical means the view that graduating high school students and school students have regarding the effectiveness of distance education modality (EAD), and the degree of significance that the popular myth wrong influence in the denial of choice the choice for this type of education in the city of Curitiba. In its theoretical foundation context and explained the relevance, procedures and scope of distance education modality in our country, it can be seen that it has reached the status of representing itself as the great teaching innovation, which requires the subject to the develops a profile on the dedication and grounded mainly on specific skills to the full success in the self-learning process. Lack of knowledge of the peculiar procedures for the EAD and the strong influence of popular myth of being an "easy and ineffective education", can provide a strong resistance for the option of admission to institutions that offer courses in this type of education. To achieve the goals aligned research, we used the methodological tool of investigative research through data collection and its respective analysis, tabulation and statistical context. It is of fundamental importance to understanding the analysis of data collected in this research because through them you can build strategies and procedures to promote distance education, which unlike the wrong labels to popular myth, it is legitimately a promising and innovative teaching model.